Protracted Morphological Changes in the Corticospinal Tract Within the Cervical Spinal Cord After Intracerebral Hemorrhage in the Right Striatum of Mice - Ng, Anson Cho Kiu; Yao, Min; Cheng, Stephen Yin; Li, Jing; Huang, Jian-Dong; Wu, Wutian; Leung, Gilberto Ka Kit; Sun, Haitao (Frontiers in Neuroscience, 2020)
Intracerebral haemorrhage (ICH) is associated with high morbidity and mortality rates. Currently, there is no promising treatment that improves prognosis significantly. Whilst a thorough investigation of the pathological process within the primary site of injury in the brain has been conducted by the research field, the focus was mainly on gray matter injury, which partly accounted for the failure of the discovery of clinically efficacious treatments. It is not until recent years that white matter injury in the brain after subcortical ICH was examined. As white matter tracts form networks between different regions, damage to fibers should impair brain connectivity, resulting in functional impairment. Although white matter changes have been demonstrated in the brain after ICH, alterations distant from the initial injury site down in the spinal cord are unclear. This longitudinal study, for the first time, revealed prolonged morphological changes of the contralesional dorsal corticospinal tract (CST) in the spinal cord five weeks after experimental ICH in mice by confocal microscopy and transmission electron microscopy, implying that structural integrity of the CST was compromised extensively after ICH. Given the important role of CST in motor function, future translational studies targeting motor recovery should delineate the effect of treatment on CST integrity.